(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2024)
We prove that for q(-1,0)(0,1), the partial theta function θ (q,x):=_j=0^∞q^j(j+1)/2x^j has no zeros in the closed unit disk.